2014
DOI: 10.1152/japplphysiol.00268.2014
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene alcohols and sterols from rice bran lower postprandial glucose-dependent insulinotropic polypeptide release and prevent diet-induced obesity in mice

Abstract: Obesity is now a worldwide health problem. Glucose-dependent insulinotropic polypeptide (GIP) is a gut hormone that is secreted following the ingestion of food and modulates energy metabolism. Previous studies reported that lowering diet-induced GIP secretion improved energy homeostasis in animals and humans, and attenuated diet-induced obesity in mice. Therefore, food-derived GIP regulators may be used in the development of foods that prevent obesity. Rice bran oil and its components are known to have benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…34) In addition, triterpene alcohols and sterols from rice bran inhibited postprandial release of glucose-dependent insulinotropic polypeptide (GIP), which promotes weight gain and insulin resistance, and prevent diet-induced obesity in mice. 35) Since γ-oryzanol is a mixture of ferulic acid esters of phytosterols and triterpene alcohols, 36) OBFR might contain higher amount of triterpene alcohols compared to WRB and increase energy expenditure via inhibition of GIP release. Moreover, rice bran contains functional components other than γ-oryzanol, phytic acid, and dietary fiber such as vitamins, essential minerals, protease inhibitors, and amylase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…34) In addition, triterpene alcohols and sterols from rice bran inhibited postprandial release of glucose-dependent insulinotropic polypeptide (GIP), which promotes weight gain and insulin resistance, and prevent diet-induced obesity in mice. 35) Since γ-oryzanol is a mixture of ferulic acid esters of phytosterols and triterpene alcohols, 36) OBFR might contain higher amount of triterpene alcohols compared to WRB and increase energy expenditure via inhibition of GIP release. Moreover, rice bran contains functional components other than γ-oryzanol, phytic acid, and dietary fiber such as vitamins, essential minerals, protease inhibitors, and amylase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that the absorption of TASP components (CA and 24Me) was slow and their blood levels reached a maximum concentration no earlier than 3–6 h after TASP ingestion in mice. Furthermore, dietary ingestion of TASP for 7 weeks did not change the metabolic gene expression levels in the skeletal muscle in mice . Therefore, dietary TASP is not likely to lower postprandial blood glucose levels by increasing glucose uptake into the skeletal muscles.…”
Section: Discussionmentioning
confidence: 98%
“…We previously demonstrated triterpene alcohol and sterol preparation (TASP) from rice bran lowered postprandial glucose‐dependent insulinotropic polypeptide (GIP) secretion and prevented obesity induced by a high‐fat diet in mice . GIP is a gut hormone secreted from enteroendocrine K cells into the bloodstream after food consumption .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the inhibitory effect of RBO may be due to the unsaponifiable matter, which downregulates SREBP-1c (Ham et al, 2016). Fukuoka et al (2014) showed that treatment of HepG2 cells with triterpene alcohols, the characteristic components of RBO, decreased the gene expression of Srebf1_v3. Moreover, the expression of Srebf1_v3 was previously reported to be directly regulated by insulin (O'Brien, Streeper, Ayala, Stadelmaier, & Hornbuckle, 2001).…”
Section: Discussionmentioning
confidence: 99%